Evaluation the effect of Oscillatoria limnetica and Chlorella vulgaris extracts and their fatty acids on pathogenic bacteria isolated from burn and surgical patients - Nesrullah, Zainab; Al-Rubaiee , Ghaidaa; Heikmat Zaki, Neihaya (Iraqi Journal of Pharmaceutical Sciences, 2024)
Antibiotic resistance has become concern for the scientific community worldwide. As a result, using natural chemicals has become an essential rather than an option in an attempt to decrease the harm caused by bacterial illnesses, which can be fatal due to the difficulties of treating them. In this study, two distinct species of microalgae (Chlorella vulgaris and Oscillatoria limnetica) were isolated from the surrounding aquatic environment. The antibacterial and antibiofilm properties of the hexane extract of these two microalgae and Chlorella vulgaris fatty acids were investigated in vitro against (Pseudomonas aeruginosa, Acinetobacter baumannii, Proteus mirabilis, and Klebsiella pneumoniae), which were clinically isolated from 100 burn and surgical patients, and diagnosis by some biochemical tests, and have been tested for resistance to antibiotics. The results showed that crude hexane extract of Chlorella vulgaris and Oscillatoria limnetica had a high effect as antibacterial and antibiofilm. Also, Chlorella vulgaris fatty acids extract showed superiority as an antibiofilm and as an antibacterial when applied at two concentrations (10 and 100 mg/ml). The important chemical components for all extracts of microalgae have been identified by Gas Chromatography-Mass Spectrometry.